(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf YHOGdbGOQ Hf CMeO Hf ecJhe Hf CMeO Hf eMeO Hf oSdje GdbjSj s)
(3ChdgG (B:s
(3JHOC HaUd(B: (3jSJKfj HMGTG hNdG hYOG GdeSJKfi CMQakG cdG hYOG HYOeG YfO ZjQ GdLQ aj s
(3BNQgG (B:s
(3GdeSCdI GdSGOSI(B: (3eG CMSf RjOkG EdG eG CTQag ajLhR HTQW EYeGd GdKGfj, hjefY Ydi EYeGd GdChd BNQ GdLRA GdNGeS jJdhg aj Chd GdLRA GdSGOS s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g``s
(3fSNI Yf fSNI GdeDdas
(3HChdgG Jedc SfI (B986(3g```s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs